STRATEGI KEPALA SEKOLAH DALAM MEMBENTUK KARAKTER SISWA - Huda, Imam Nur (STKIP Pesisir Selatan, 2025)
This study aims to outline effective principal strategies in shaping students’ character as a response to the challenges posed by rapid social changes and the digital era in character education. The research employs a literature review method, analyzing various credible sources including books, national and international journal articles, and recent educational regulations. The findings reveal that student character development heavily depends on the integration of strengthening a religious and conducive school culture and environment, management and leadership by principals that is participative and structured, as well as the influence of both external and internal factors such as technology, parental involvement, and peer interactions. Principal strategies should encompass integrated character habituation programs, maintaining collaborative communication with all stakeholders, and managing adaptive and contextual character-based curricula. The novelty of this study lies in the comprehensive synthesis of principal strategies that combine cultural, leadership, and socio-technological dynamics, emphasizing the principal’s role as a change agent who facilitates holistic synergy in character education within schools. This study provides practical recommendations for stakeholders to enhance the effectiveness of character education amid a globally dynamic environment.